MENGGABUNGKAN METODE RBF, ARIMA DAN DOUBLE EXPONENTIAL SMOOTHING UNTUK PERAMALAN KURS RUPIAH - I Nyoman Sumerta Yasa; I Nyoman Bagus Suweta Nugraha (LPPM Sekolah Tinggi Teknologi Indonesia Tanjungpinang, 2021)
Forecasting is an integral part of management decision-making activities. Forecasts are made generally based on the data of the past that were analyzed by using certain methods. Therefore in this research will predict time series data using Radial Basis Fuction, ARIMA and Double Exponential Smoothing using Matlab version 8.1. The data used is the daily selling rate of Rupiah against the UERO that started from June 2020 to January 2021. Of the three results forecast, will be used prediction results are combined by hybrid methods. From the results of RBF forecasting, ARIMA, Double Exponential Smoothing obtained MAPE respectively 0.43%, 1.49% and 0.46% and after combined with methods hybridization obtained MAPE of 0.39%. It can be seen that for the best MAPE obtained by hybrid methods. Hopefully this research can help in analyzing the fluctuation of the value of a particular currency movements at the time of transaction - purchase of foreign currency